Mitochondrial genome insights into the spatio-temporal distribution and genetic diversity of Dendrobium hancockii Rolfe (Orchidaceae) - Hou, Zhenyu; Wang, Mengting; Jiang, Yu; Xue, Qingyun; Liu, Wei; Niu, Zhitao; Ding, Xiaoyu (Frontiers in Plant Science, 2024)
With its distinctive evolutionary rate and inheritance patterns separate from the nuclear genome, organelle genome analysis has become a prominent focus of current research. Not only is it the first complete circular mitochondrial genome published in the Dendrobium genus, but we've also employed the mitochondrial genome of Dendrobium hancockii Rolfe as a foundation for comparative genomics, genetic diversity, and floristic geography studies. Initially, we constructed a circular mitochondrial map spanning 523,952 bp, containing 40 unique protein-coding genes (PCGs), 37 transfer RNA (tRNA) genes, and 4 ribosomal RNA (rRNA) genes.Additionally, comparative analysis involved mitochondrial genes from 26 land plants, revealing a conserved gene cluster segment, "rpl16-ccmFn-rps3-rps19," within the Dendrobium genus. The mitochondrial genome exhibits a lower point mutation rate and a higher structural variation pattern Simultaneously, we utilized mitochondrial and nuclear genes to explore genetic diversity and structure across 103 samples from 23 wild populations of D. hancockii. The data unequivocally divided D. hancockii into two major groups, supported by evidence from population diversity, genetic structure analysis, principal component analysis (PCA), and phylogenetic trees. The publication of D. hancockii 's complete mitochondrial genome not only fills a crucial gap in our understanding of orchid mitochondrial genomes but also lays the groundwork for subsequent molecular marker research. Furthermore, it reveals the research potential for genetic differentiation, providing insights into the species' evolutionary history and phytogeography from a mitochondrial perspective.